Physical Education and Its Scope: A Literature Review of Empirical Studies with A Holistic Perspective Teaching Practices in Indonesia - Uray Gustian; Deddy Rahmat Saputra; Cece Rakhmat; Yusi Rika Yustiana; Intan Primayanti (Indonesian Journal of Physical Education and Sport Science)
Study purpose. Physical Education (PE) is a part of sports education that places body movement as the main principle of learning whose outcomes include cognitive, motoric, affective, and social. Extensive research has been conducted to find the ideal PE teaching concept. The literature review aimed to gather information about existing studies in Indonesia in an effort to achieve PE learning objectives.